2017
DOI: 10.3389/fncel.2016.00306
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of a Smoothened Receptor Agonist against Early Brain Injury after Experimental Subarachnoid Hemorrhage in Rats

Abstract: The sonic hedgehog (Shh) signaling pathway plays a fundamental role in the central nervous system (CNS) development, but its effects on neural cell survival and brain repair after subarachnoid hemorrhage (SAH) has not been well-investigated. The present study was undertaken to evaluate the influence of an agonist of the Shh co-receptor Smoothened (Smo), purmorphamine (PUR), on early brain injury (EBI) as well as the underlying mechanisms after SAH. PUR was administered via an intraperitoneal injection with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
(50 reference statements)
2
23
1
Order By: Relevance
“…Taken together, blocking microglial activation may contribute to the neuroprotective effects of PUR in immature brain in mice following HI. The capacity for PUR to exert antioxidant effects in HI, as revealed by significantly decreasing HI-induced ROS levels, was consistent with a previous study (Hu et al, 2016). A number of antioxidants, including allopurinol, erythropoietin, resveratrol, and omega-3 fatty acids, have been shown to exhibit neuroprotective properties in different animal models of perinatal HI brain injury (Peeters-Scholte et al, 2003;Arteaga et al, 2017;Revuelta et al, 2017).…”
Section: Neuronal Cell Death and Neuro-inflammation Were Attenuated Fsupporting
confidence: 90%
See 3 more Smart Citations
“…Taken together, blocking microglial activation may contribute to the neuroprotective effects of PUR in immature brain in mice following HI. The capacity for PUR to exert antioxidant effects in HI, as revealed by significantly decreasing HI-induced ROS levels, was consistent with a previous study (Hu et al, 2016). A number of antioxidants, including allopurinol, erythropoietin, resveratrol, and omega-3 fatty acids, have been shown to exhibit neuroprotective properties in different animal models of perinatal HI brain injury (Peeters-Scholte et al, 2003;Arteaga et al, 2017;Revuelta et al, 2017).…”
Section: Neuronal Cell Death and Neuro-inflammation Were Attenuated Fsupporting
confidence: 90%
“…In addition, the endogenous Shh pathway in the cortex and hippocampus was reported to be upregulated in response to stroke and ischemic insult (Sims et al, 2009;Chechneva et al, 2014). However, Shh expression in the cortex was downregulated in the early stages after experimental subarachnoid hemorrhage (Zuo et al, 2015;Hu et al, 2016). In the present study, the expression of Shh signaling including Shh and Ptch within brain was reduced following HI insult.…”
Section: Pur Restored Levels Of Shh Signaling After Himentioning
confidence: 43%
See 2 more Smart Citations
“…PUR, which has also been shown to promote blood-brain barrier formation, plays a crucial role in activation of the endogenous anti-inflammatory system within the CNS [ 9 ], and recent findings have indicated that PUR protects cortical neurons and restores neurological deficits after ischemic stroke in rats [ 10 ]. It has been reported by us that PUR exerted neuroprotection against subarachnoid hemorrhage-induced injury in adult rats [ 11 ] and hypoxia-ischemia in neonatal mice [ 12 ].…”
Section: Introductionmentioning
confidence: 99%